Vitamin K – a scoping review for Nordic Nutrition Recommendations 2023 - Lyytinen, Arja T; Linneberg, Allan (Food & nutrition research, 2023)
Vitamin K occurs in dietary supply in two major forms: phylloquinone (vitamin K1) and menaquinones (collectively referred as vitamin K2). Phylloquinone is derived from plants. There are at least 10 forms of menaquinones varying in chain length and they are produced by bacteria except menaquinone-4. Menaquinone-4 is formed from phylloquinone or other menaquinone forms. Phylloquinone is considered to be the major contributor and menaquinones are thought to contribute less to vitamin K intake in Western diets. However, less is known about the content of menaquinones than phylloquinones in foods. Vitamin K is known to function as an enzymatic cofactor in the gamma-carboxylation of vitamin K dependent proteins (VKDPs). Hepatic VKDPs are involved in coagulation. Extrahepatic VKDPs have a role e.g. in bone health and vascular calcification. However, the amount of vitamin K needed for optimal functioning of the different VKDPs is not known.